PENGARUH HEDONIC SHOPPING MOTIVATION DAN SALES PROMOTION TERHADAP POSITIVE EMOTION SERTA DAMPAKNYA PADA IMPULSE BUYING - Indarni, Chindy Cherly; Susanta, Susanta; Hadi, Lukmono (Jurnal Ilmu Administrasi dan Bisnis, 2020)
This research was conducted to determine the effect of Hedonic Shopping Motivation and Sales Promotion on Positive Emotion and its Impact on Impulse Buying. The sample size in this study was 69 respondents. The sampling technique used is Non Probability Sampling with purposive sampling  for  an  infinite  population.  The  data  analysis  technique  used  descriptive  statistical analysis  and  inferential  statistical  analysis  using the statistical  method  of  Structural Equation Modeling  using  SmartPLS  3.0.  The  results  of  this  study  conclude  that  Hedonic  Shopping Motivation has a significant effect on Positive Emotion, Sales Promotion has a significant effect on Positive Emotion, Hedonic Shopping Motivation has a significant effect on Impulse Buying, Sales Promotion has a significant effect on Impulse Buying, Positive Emotion has a significant effect on Impulse Buying. , Miniso Malioboro Mall Yogyakarta must pay attention to the stimuli used to increase sales. The way this is done is, among others, by providing stimuli that can make consumers feel happy with products, services, and sales promotions provided by Miniso so as to encourage consumers to do Impulse Buying while inside Miniso Malioboro Mall Yogyakarta.